Aspek Biologi Ikan Sepongkah (Ambassis nalua Hamilton, 1882) - Shonia Ritonga; Khairul Khairul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to examine the biological aspects of Sepongkah Fish (Ambassis nalua) in the Bilah River and determine the condition of the population. The method used in this research is purposive sampling. Fish samples were taken using a splint net. The fish caught were measured for their total length with a ruler and weighed with a digital scale. The results showed that the size classes of small, medium and large fish were 93, 30 and 2 individuals, respectively, with a length-weight relationship obtained, namely b = 0.2577 and R² = 0.9643. The sex ratio of male and female fish found was 2:1. In conclusion, the biological aspects of Sepongkah Fish in the Lower Bilah River still show a fairly good condition. Keywords: Ambassis nalua, Biological Aspect, Sungai Bilah